Tracking systems in logistics - Nagy, Sándor; Tamás, Péter (Advanced Logistic Systems - Theory and Practice, 2024)
With the spread of globalization, there is an increasing need for unique identification and traceability of products. This affects all elements of the supply chain, including warehousing. Identification of products, means of transport and storage facilities is a fundamental need in warehouse processes. Without it, modern industrial operations are unthinkable. With the advance of Industry 4.0, new technologies and new solutions have emerged, which can be applied when modernizing or designing a new system, weighing up the advantages and disadvantages. Our publication tries to help by describing and comparing the different systems. In addition to the three most common solutions, we also look at the developments expected in the near future, which are extensions and improvements of the current systems.